PUBLIC POLICY EVALUATION AND ENVIRONMENTAL GOVERNANCE OF THE REMPANG ECO CITY PROJECT : LESSONS FROM A CONTESTED NATIONAL STRATEGIC PROJECT IN INDONESIA - Rika Meriza; Yustina Yustina (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze public policy evaluation and environmental governance issues surrounding the Rempang Eco City Project in Indonesia, particularly following its exclusion from the National Strategic Project agenda. The research employs a qualitative approach using a case study method and systematic literature review from government regulations, scientific journals, environmental organization reports, official investigations, and national media coverage related to Rempang Island. Data were analyzed using public policy and environmental mitigation perspectives. The findings indicate that the Rempang Eco City policy generated serious social conflicts, ecological threats, and legal uncertainty due to weak community participation during the policy formulation process. From an environmental mitigation perspective, the industrialization of Rempang Island has the potential to trigger coastal ecosystem destruction, air and water pollution, coastal abrasion, loss of fishermen’s livelihoods, and prolonged social conflict. The government’s recent decision to remove Rempang Eco City from the National Strategic Project list is considered an important corrective policy. However, unresolved legal and environmental governance issues remain. Policy evaluation based on effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness demonstrates that the Rempang Eco City policy failed to fulfill the principles of sustainable development and good governance.